RELATIONSHIP BETWEEN NUTRITIONAL INTAKE AND SMOOTH BREASTFEEDING OF MOTHERS WHO HAVE BABIES AGED 0-6 MONTHS - Hayati, Sri; Rahayu, Intan Nurmayanti; Iklima, Nurul (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2023)
Breast milk is the first liquid food produced naturally by the breast. The problem most often by breastfeeding mothers is smooth breastfeeding. Factors that influence smooth breastfeeding include nutrition, mother's age, parity status, baby's birth weight, baby's birth age, and use of contraceptives. The nutrition consumed by the mother is related to the volume of breast milk produced per day. This research aims to determine the relationship between nutritional intake and smooth breast milk production in breastfeeding mothers 0-6 months. This research was in July 2023 in Puskesmas Ujung Berung Indah. The design is the quantitative correlation with a cross-sectional. The population was 287 breastfeeding mothers 0-6 months. The sample was 50 respondents using a non-probability purposive sampling. The instrument used a questionnaire with a Chi-Square test. The results are the majority (78%) have adequate nutritional intake and the majority (68%) with smooth breast milk production. The conclusion is a relationship between nutritional intake and the smooth production of breast milk with a p-value of 0.002. Suggestions for education programs on nutritional intake of breastfeeding mothers.